2009
DOI: 10.1371/journal.pone.0007977
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pancreatic Carcinomas by Imaging Lactose-Binding Protein Expression in Peritumoral Pancreas Using [18F]Fluoroethyl-Deoxylactose PET/CT

Abstract: BackgroundEarly diagnosis of pancreatic carcinoma with highly sensitive diagnostic imaging methods could save lives of many thousands of patients, because early detection increases resectability and survival rates. Current non-invasive diagnostic imaging techniques have inadequate resolution and sensitivity for detection of small size (∼2–3 mm) early pancreatic carcinoma lesions. Therefore, we have assessed the efficacy of positron emission tomography and computer tomography (PET/CT) imaging with β-O-D-galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Furthermore, micro single-photon emission CT/CT is already used in the clinic, so that this plectin probe may be quickly adapted for human use. In another approach, it was shown that it is possible to image increased levels of pancreatitis-associated protein (PAP), which is expressed in pancreatic acinar cells surrounding foci of pancreatic cancer or pancreatic inflammation, using ( 18 F)-fluoroethyl-deoxylactose (FDG) positron emission tomography 37. The localisation of PAP has the advantage that the area occupied by cells expressing this molecule is much greater than the volume of the cancer cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, micro single-photon emission CT/CT is already used in the clinic, so that this plectin probe may be quickly adapted for human use. In another approach, it was shown that it is possible to image increased levels of pancreatitis-associated protein (PAP), which is expressed in pancreatic acinar cells surrounding foci of pancreatic cancer or pancreatic inflammation, using ( 18 F)-fluoroethyl-deoxylactose (FDG) positron emission tomography 37. The localisation of PAP has the advantage that the area occupied by cells expressing this molecule is much greater than the volume of the cancer cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…To establish pancreatic tumor xenografts in nude mice, human L3.6pl pancreatic cancer cells were stably transduced with a retroviral vector bearing dual reporter gene GL, a tandem fusion of the green fluorescence protein and firefly luciferase genes, as previously reported [18]. Transduced L3.6pl-GL + cells were selected by fluorescence-activated cell sorting and their fluorescence and bioluminescence properties were characterised as previously described [22].…”
Section: Methodsmentioning
confidence: 99%
“…Tumor implantation was performed as previously described [18]. Briefly, 4- to 6-week-old athymic nude mice (n=15, Charles River Laboratories) were anaesthetised by isoflurane inhalation (2–2.5% in oxygen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Zhao et al (139) reported earlier detection of pancreatic cancer xenografts with 11 C-acetate PET than with FDG PET, but the ratio of radiotracer accumulation between tumor and nontumor in 11 C-acetate PET was lower than that in FDG PET during the same period. Another radiotracer, 18 F-FEDL, which is overexpressed in peritumoral pancreatic acinar cells, was reported to be helpful for detection of small pancreatic cancer lesions (140). Additional studies are needed to evaluate the performance of new radiotracers for detecting and characterizing pancreatic cancer specifically.…”
Section: Review: Pancreatic Ductal Adenocarcinoma: In Vitro Diagnostimentioning
confidence: 99%